The Impact of Strategic Corporate Social Responsibility on Organizational Resilience—An Exploratory Case Study Based on Tesla - Xiaoping Liu; Yishu Zhou (Administrative Sciences, 2025)
In today’s complex business environments, integrating strategic corporate social responsibility (SCSR) is essential for aligning business objectives with societal interests and strengthening organizational resilience. Using Tesla as a case study, we applied stakeholder theory, grounded theory, and the Stimulus-Organism-Response (S-O-R) model to construct a theoretical framework on the impact of SCSR on organizational resilience and to examine the mechanisms underpinning this process. Through the implementation of SCSR, enterprises deeply engage with primary and public stakeholders, establish resilient relationships, and enhance organizational resilience through seven dimensions: development governance, strategic management, relationship, financial, product, cultural, and social. The theoretical framework developed in this study provides a reference for subsequent research on SCSR and organizational resilience, and offers management insights for enterprises to integrate SCSR, enhance organizational resilience, and improve long-term competitiveness.